2020
DOI: 10.1002/art.41289
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Interleukin‐27–Mediated Control of CD4+ T Cell Function Impact on Ectopic Lymphoid Structure Formation in Patients With Sjögren's Syndrome

Abstract: Objective Ectopic lymphoid structures (ELS) develop at sites of infection, autoimmunity, and cancer. In patients with Sjögren's syndrome (SS), ELS support autoreactive B cell activation and lymphomagenesis. Interleukin‐27 (IL‐27) is a key regulator of adaptive immunity and limits Th17 cell–driven pathology. We undertook this study to elucidate the role of IL‐27 in ELS formation and function in autoimmunity using a murine model of sialadenitis and in patients with SS. Methods ELS formation was induced in wild‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Other authors showed that the absence of IL-27 signaling (an immunomodulatory cytokine mainly produced by resident myeloid cells) led to an uncontrolled Th17 expansion in the glands, which in turn fostered an exaggerated expansion and aberrant activity of salivary glands (ectopic lymphoid structures). In SS, they found that despite pSS patients expressing high local and peripheral levels of IL-27, this cytokine was unable to inhibit Th17 differentiation and conversely induced a strong IFNγ response compared to healthy donors [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors showed that the absence of IL-27 signaling (an immunomodulatory cytokine mainly produced by resident myeloid cells) led to an uncontrolled Th17 expansion in the glands, which in turn fostered an exaggerated expansion and aberrant activity of salivary glands (ectopic lymphoid structures). In SS, they found that despite pSS patients expressing high local and peripheral levels of IL-27, this cytokine was unable to inhibit Th17 differentiation and conversely induced a strong IFNγ response compared to healthy donors [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by observations in rheumatoid arthritis where the pro‐inflammatory role of IL‐6 contrasts with the more nuanced contribution of IL‐27, which inhibits the formation of ectopic lymphoid structures within the inflamed synovium [93]. Similar studies in T cells emphasize the opposing functions of IL‐6 and IL‐27 in determining the effector characteristics of CD4 + T cells [92–96]. At least in part, these differences are attributable to structural and sequence differences between the cytokine receptors.…”
Section: The Complexities Linked To Jak‐stat Signallingmentioning
confidence: 96%
“…Tissue-derived factors that may regulate IL-17A expression in CD4 − and CD4 + T cell compartments include IL-27. Thus, IL-27 display an inhibitory effect on IL-17A secretion in PBMC cultures of SS patients and not RA patients or age-matched healthy donors [ 121 ]. Further, induction of experimental sialadenitis in IL-27receptor subunit alpha knockout mice aggravates the formation of ectopic lymphoid structures in SGs, as compared to wild-type mice, a finding that can be restored by IL-17A neutralization [ 121 ].…”
Section: The Role Of Il-17a In Sjögren's Syndromementioning
confidence: 99%